The Design of Morphological/ Linguistic Data in L1 and L2 Monolingual, Explanatory Dictionaries: A Functional and/or Linguistic Approach? - Swanepoel, P.H. (Lexikos, 2015)
The contributions in Klosa (2013a) provide information on various aspects of the design of morphological data for (German) language dictionaries. Bergenholtz and Gouws (2013), however, reject most of these contributions as sources lexicographers could use for the design of language dictionaries because they are guided by linguistic theory (cf. their critique of Klosa 2013b), instead of Function Theory, and by a misguided application of methods for user research, (cf. their critique of Töpel's 2013 use of the questionnaire as method for user research). The first goal of this article is to provide a critical discussion of Bergenholtz and Gouws's (2013) views on the approach of Function Theory to the theoretical, methodological and practical aspects of the design of morphological/linguistic data in L1/L2 (language) dictionaries. It is argued that the approach of Function Theory provides lexicographers only with a usable overview of the design trends in printed and electronic dictionaries for the selection and presentation of morphological/ linguistic data in dictionaries, but that the theoretical, methodological and practical approach of Function Theory is fraught with difficulties. The strategy Bergenholtz and Gouws (2013) use to debunk the linguistic approach to lexicography is not new; it is a well-known strategy used in the rhetoric of Function Theory. The second goal of this article is therefore to point out some of the general problems with a Function Theory of lexicography for the planning, production and publishing of language dictionaries. Given the problems with the theoretical, methodological and practical aspects of Function Theory, it does not offer a viable alternative to the linguistic approach to the design of morphological/linguistic data in L1/L2 (language) dictionaries. It is argued that linguistic lexicography provides lexicographers with access to a vast body of theoretical, methodological and practical research to support the design of morphological data in L1/L2 (language) dictionaries. Furthermore, it is argued that Function Theory has established the importance of functional variables in the design of (language) dictionaries, but that what lexicography needs now is a truly multidisciplinary approach to lexicography, and not an approach that reduces lexicography to the status of a hand-maiden of another discipline, for example, information science, or of a reductionist Function Theory of lexicography.